2015
DOI: 10.3390/ma8063101
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescent ZnO Nanoparticles and Their Biological Applications

Abstract: During the past decades, numerous achievements concerning luminescent zinc oxide nanoparticles (ZnO NPs) have been reported due to their improved luminescence and good biocompatibility. The photoluminescence of ZnO NPs usually contains two parts, the exciton-related ultraviolet (UV) emission and the defect-related visible emission. With respect to the visible emission, many routes have been developed to synthesize and functionalize ZnO NPs for the applications in detecting metal ions and biomolecules, biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
131
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(134 citation statements)
references
References 148 publications
2
131
0
1
Order By: Relevance
“…ZnO NP is a less toxic and low-cost nanoparticle that can be used in many fields that include antibacterial, antifungal, antioxidant, and anticancer ones [24,25]. The antibacterial activity of ZnO NP was dependent on their capability to activate excess ROS generation such as superoxide anion, hydrogen peroxide, and hydroxyl radical generation [26]. ZnO NP antibacterial activity may associate with the accretion in bacterial cells cytoplasm and promote the release of Zn 2+ .…”
Section: Characterization Of Zinc Oxide Nanoparticlesmentioning
confidence: 99%
“…ZnO NP is a less toxic and low-cost nanoparticle that can be used in many fields that include antibacterial, antifungal, antioxidant, and anticancer ones [24,25]. The antibacterial activity of ZnO NP was dependent on their capability to activate excess ROS generation such as superoxide anion, hydrogen peroxide, and hydroxyl radical generation [26]. ZnO NP antibacterial activity may associate with the accretion in bacterial cells cytoplasm and promote the release of Zn 2+ .…”
Section: Characterization Of Zinc Oxide Nanoparticlesmentioning
confidence: 99%
“…68 There are two major types of tattoo pigments in clinical use but with significant limitations: (i) conventional carbon graphite and India ink, 6 which are cosmetically unappealing and may be mistaken for a melanocytic lesion, and (ii) fluorescent particles (e.g., ZnO or dye-doped poly(methyl methacrylate) (PMMA) particles), 7,8 which can only be visualized under UV light. To permanently remove these long-lasting fluorescent tattoo marks, 9,10 laser or surgical treatments are often needed. In addition, both tattoo pigments may cause local inflammatory responses ( e.g ., dermatitis), leading to discomfort at the tattoo sites.…”
mentioning
confidence: 99%
“…The same antimicrobial effect was observed till 5 days of incubation. Similarly, it has been reported that the commendable antimicrobial activity of the composite relays on the presence of nanoZnO particles in the matrix where Zn 2+ ions attack the negatively charged cell wall and will lead to leakage and ultimately in death of bacteria [35].…”
Section: Antimicrobial Properties Of Neat and Znse Nanoparticles Incomentioning
confidence: 87%